Carfilzomib, cyclophosphamide, and dexamethasone (KCd) for the treatment of triple‐class relapsed/refractory multiple myeloma (RRMM). (31st August 2021) - Pennipede, Dante; Mohyuddin, Ghulam Rehman; Hawkins, Ryan; Ganguly, Siddhartha; Shune, Leyla; Ahmed, Nausheen; Mohan, Meera; Cui, Wei; Mahmoudjafari, Zahra; McGuirk, Joseph; Atrash, Shebli; Abdallah, Al‐Ola
Abstract: Background: Multiple myeloma (MM) is an incurable hematologic malignancy, and outcomes remain poor for patients with triple‐class relapsed/refractory MM (RRMM). Descriptive analyses were performed on available data for patient characteristics, disease course, and outcomes of the KCd on triple‐class RRMM patients at our institution. Patients and Methods: Twenty‐three patients with triple‐class RRMM treated with KCd between June 2017 and October 2020 were included in our analysis. The regimen KCd consisted of 28 days cycles of carfilzomib 20/36 mg/m 2 IV on days 1, 2, 8, 9, 15, and 16, cyclophosphamide 300 mg/m2 IV weekly, and dexamethasone (20‐40) mg orally weekly. Results: Patients received a median of 6 (3‐10) prior regimens. The median number of cycles administered was 4 (1‐11) cycles. Overall response rate was 52%, 6 patients (26%) achieved very good partial response (VGPR), 6 patients (26%) achieved partial response (PR), and 5 patients (22%) achieved stable disease (SD). Progression‐free survival (PFS) and Overall‐survival (OS) were 4 and 11.9 months, respectively. There was no reported treatment‐related mortality. The most common grade ≥3 adverse events were neutropenia (26%), thrombocytopenia (56.5%), and anemia (56.5%). Conclusions: KCd showed clinically meaningful efficacy and manageable safety profile in patients with triple‐class RRMM in real‐world.